The Effect OF FDR, NPF, OEOI, and Size Toward ROA (Comparative Study on Indonesian Islamic Bank and Malaysian Islamic Bank Period 2010-2015) - Windriya, Anafil (International Journal of Islamic Business and Economics (IJIBEC), 2019)
This research aims to analyze the influence of Financing to Deposit Ratio (FDR), Non Performing Financing (NPF), Operating Expenses to Operating Income (OEOI), Firm Size toward Return On Asset (ROA). The object of this research are Islamic Bank in Indonesia and Islamic Bank in Malaysia in 2010-2015. Another aim is to determine whether there are differences in effects of FDR, NPF, OEOI and size toward ROA between Islamic Bank in Indonesia and Islamic Bank in Malaysia. Multiple linear regression analysis was used to test the hypothesis in this study. Chow test is used to determine the differences in the effect. The results of this study concluded that FDR, NPF, OEOI and Size effect on ROA simultaneously, both at Indonesian Islamic Bank and Malaysian Islamic Bank. In Indonesian Islamic Bank, independent variables that influence toward ROA are FDR, OEOI and Size. In Malaysia Islamic Bank, only OEOA wich affecting toward ROA. Based on the chow test, can be concluded that there is a significant difference between the Indonesian Islamic Bank and Malaysian Islamic Bank. Results of independent t test showed that the average variable that has a different effect between Indonesia Islamic Banks and Malaysia Islamic Banks is Size.